2020
DOI: 10.1002/prp2.571
|View full text |Cite
|
Sign up to set email alerts
|

Utility of accumulated opioid supply days and individual patient factors in predicting probability of transitioning to long‐term opioid use: An observational study in the Veterans Health Administration

Abstract: Initial supply days dispensed to new users is strongly predictive of future long-term opioid use (LTO). The objective was to examine whether a model integrating additional clinical variables conferred meaningful improvement in predicting LTO, beyond a simple approach using only accumulated supply. Three cohorts were created using Veteran's Health Administration data based on accumulated supply days during the 90 days following opioid initiation: (a) <30 days, (b) ≥30 days, (c) ≥60 days. A base, unadjusted prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The findings from this study are consistent with prior work which has identified that higher levels of acute opioid exposure, including longer initial treatment duration and higher prescribed doses, are associated with increased risk for transition to LTO (Deyo et al, 2017;Hadlandsmyth et al, 2003;Hadlandsmyth, Mosher, Vander Weg, et al, 2020;Mosher et al, 2018;Shah et al, 2017;Weiner et al, 2020). Implications of these findings for practice have resulted in reductions in acute opioid prescribing, at times under legislative mandate (Davis et al, 2019;Guy Jr et al, 2017;Hadlandsmyth et al, 2018); however, the need for acute pain management remains, and poor acute pain management is a risk factor for transition to chronic pain (Gan, 2017;Kehlet et al, 2006;McGreevy et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings from this study are consistent with prior work which has identified that higher levels of acute opioid exposure, including longer initial treatment duration and higher prescribed doses, are associated with increased risk for transition to LTO (Deyo et al, 2017;Hadlandsmyth et al, 2003;Hadlandsmyth, Mosher, Vander Weg, et al, 2020;Mosher et al, 2018;Shah et al, 2017;Weiner et al, 2020). Implications of these findings for practice have resulted in reductions in acute opioid prescribing, at times under legislative mandate (Davis et al, 2019;Guy Jr et al, 2017;Hadlandsmyth et al, 2018); however, the need for acute pain management remains, and poor acute pain management is a risk factor for transition to chronic pain (Gan, 2017;Kehlet et al, 2006;McGreevy et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Within the Veteran's Administration (VA), even as overall opioid prescribing has reduced in recent years, the relationship between early prescribing patterns and the likelihood of transitioning to LTO has remained stable (Hadlandsmyth et al, 2003). While multiple prior studies have identified characteristics of early opioid prescribing that predict future risk for progression to LTO, (Deyo et al, 2017; Hadlandsmyth et al, 2003; Hadlandsmyth, Mosher, Vander Weg, et al, 2020; Mosher et al, 2018; Shah et al, 2017; Weiner et al, 2020) this approach does not consider how these individual characteristics tend to cluster together in practice and what key characteristics may differentiate these clusters. Thus, the current study will explore clusters of early opioid prescribing as a complement to existing approaches that treat risk variables as independent factors.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with multiple prior studies in which the days of prior opioid use is often the most significant predictor of subsequent LTO. 6 25 26 27 28 29 These findings underscore the importance of multimodal perioperative pain management and prescribing short timeframes of opioids, adjusting as needed. 3 30…”
Section: Discussionmentioning
confidence: 93%
“…Preoperative COU was defined as > 25% nonzero days (calculated using the cabinet supply method) in the 180 days before surgery admit date time (> 45 nonzero days) or ≥ 1 opioid prescription for ≥ 28-day supply released within 90 days before surgery date. 12,13 For NOU pa-tients, the postoperative outcome of interest was new postoperative prolonged opioid use. This was defined by Page and colleagues as ≥ 1 opioid prescription released between surgery discharge date and postdischarge day 44, ≥ 1 opioid prescription released between postdischarge day 45 and 89, and ≥ 1 opioid prescription released between postdischarge day 90 and 180.…”
Section: Patient Cohortsmentioning
confidence: 99%